Hidden histories made visible? Reflections on a geographical exhibition. Issue 3 (16th May 2012) - Driver, Felix
<x xml:space="preserve">Abstract</x> This paper addresses the potential of public exhibitions to challenge long taken‐for‐granted assumptions about the history of exploration and geography. The Hidden Histories of Exploration exhibition, originally held in 2009, was based on historical research in the Royal Geographical Society's extensive collections, including manuscripts, books, maps and atlases, artefacts, artworks, photography and film. The exhibition was designed to reveal the agency of indigenous peoples and intermediaries in the history of exploration, as reflected especially in the recruitment of guides, interpreters, porters and pilots. By highlighting and to some extent celebrating the role of such individuals, it sought to prompt questions about what is made visible and what is obscured in standard narratives of exploration, especially when seen from a metropolitan perspective. However, the relationship between research and exhibition was by no means one‐way, as is implied by the language of 'dissemination' and 'output': the process of bringing the exhibition into being raised questions about the structure of the archives on which the exhibition depended, as well as prompting further reflection on the biographical mode in which the work of recovery of 'hidden histories' is often conceived in the heritage sector. Particular attention is devoted to the impact of collaboration with designers on the presentation and interpretation of materials in the exhibition. The paper focuses on three design strategies reflected in the exhibition space: 'role reversal' (celebrating the role of intermediaries and presenting the explorers as dependent); 'juxtaposition' (emphasising the importance of partnership and the co‐production of geographical knowledge); and 're‐scaling' (transforming anonymous archival fragments into documents of a truly human history).